Encounters ü Materialities ü Confrontations : Archaeologies of Social Space and Interaction. - Cornell, Per (Cambridge Scholars Publishing, 2007)
This collection of texts is a first step towards providing a theoretical and methodological platform for the study of social encounters. The social encounter is a particular sort of concept, focusing on confusion, tension, trauma, and possibly social change that may emerge in situations of contact when people and things interact. A social encounter is, however, not only about negotiation or contemplating existence, but is rather about what happens when people interact actively, when they invo ...